The Elements and Color of Lacustrine Record Revealed Lake Environmental Changes in Semiarid Northern China: A Case Study From Chagan Nur Lake of Southern Mongolian Plateau - Wang, Zhong; Li, Guoqiang; Wang, Xiaoyan; Gou, Siyi; Deng, Yanqing; Tao, Shuxian; Zhang, Yunian; Yang, He; Zhao, Wenwei; Jin, Ming (Frontiers in Earth Science, 2021)
The lakes at the southern Mongolian Plateau are sensitive to the variation of EASM changes during the Holocene, and hence the lacustrine records of these lakes provide prospects for understanding how lake environmental changes respond to EASM variation at different timescales. The interpretation of proxy indexes of lacustrine sediments is complex due to the various climatic or/and environmental factors influencing the processes during deposition and after deposition. In this study, the elements and colors of an 11.7-m lacustrine record from Chagan Nur at the southern Mongolian Plateau of northern China were analyzed to constrain the lake environmental changes during the Holocene. The results show that stable elements of Al, Si, K, Ti, Fe, and Rb are more related to surface erosion or/and vegetation coverage, and the variation of Sr is related to the lake-level change in Chagan Nur. The element and color of the lacustrine records show that a small and shallow lake environment occurred at Chagan Nur during 11.7–10.5 ka, the lake level had increased during 10.5–7 ka, and then the lake shrank with strength surface erosion during 7–6.2 ka and from 2 ka to the present. The lake level and surface erosion changes of Chagan Nur have shown a direct response to EASM precipitation changes as reconstructed from the pollen record from the Chagan Nur Lake and other records from northern China.